Exploring the mechanism of empathy on lens language and linguistic landscape on movie-induced tourism: The moderating effect of cultural differences - Zeng, Yanqin; Xu, Ziqi; Chen, Liang; Huang, Yunxi (Frontiers in Psychology, 2023)
Research on movie-induced tourism is getting more and more profound, but there is rarely any research on the inner mechanism of audience's empathy for the movie scenes. This article argues that the movie's lens language contributes to the communication between the movie and the audience, which not only helps the audience shape their imagination of the movie scenes, but also contributes to the construction of virtual linguistic landscapes, and promotes the audience to bring their emotions and self-expression into the story, ultimately enhancing the audience's perception of the shooting locations. This article also proposes cultural differences as a factor regulating audience empathy. The findings show that there is a clear logical relationship between lens language and linguistic landscape under the effect of empathy, and cultural differences are indeed an important factor in moderating audience' s empathy for movie scenes and shooting locations.